A Recombinant Subviral Particle-Based Vaccine Protects Magpie (Pica pica) Against West Nile Virus Infection - Jiménez de Oya, Nereida; Escribano-Romero, Estela; Camacho, María-Cruz; Blazquez, Ana-Belén; Martín-Acebes, Miguel A.; Höfle, Ursula; Saiz, Juan-Carlos (Frontiers in Microbiology, 2019)
The mosquito-borne West Nile virus (WNV) is a highly neurovirulent Flavivirus currently representing an emergent zoonotic concern. WNV cycles in nature between mosquito vectors and birds that act as amplifier hosts and play an essential role in virus ecology, being a threat to many species. Availability of an efficient avian vaccine would benefit certain avian populations, both birds grown for hunting and restocking activities, as well as endangered species in captive breeding projects, wildlife reservations and recreation installations, and would be useful to prevent and contain outbreaks. Avian vaccination would be also of interest to limit WNV spillover to humans or horses from susceptible bird species that live in urbanized landscapes, like magpies. Herein we have addressed the efficacy of a single dose of a WNV recombinant subviral particle (RSP) vaccine in susceptible magpie (Pica pica). The protective capacity of the RSP-based vaccine was demonstrated upon challenge of magpies with 5x103 plaque forming units of a neurovirulent WNV strain. A significant improvement in survival rates of immunized birds was recorded when compared to vehicle-inoculated animals (71.4% vs 22.2%, respectively). Viremia, which is directly related to the capacity of a host to be competent for virus transmission, was reduced in vaccinated animals, as was the presence of infectious virus in feather follicles. Bird-to-bird transmission was recorded in three of six unchallenged (contact) magpies housed with non-vaccinated WNV-infected birds, but not in contact animals housed with vaccinated WNV-infected magpies. These results demonstrate the protective efficacy of the RSP-based vaccine in susceptible birds against WNV infection and its value in controlling the spread of the virus.